Implications of High Rates of Metastatic Prostate Cancer in BRCA2 Mutation Carriers. Issue 13 (26th May 2016) - Gleicher, Stephanie; Kauffman, Eric C.; Kotula, Leszek; Bratslavsky, Gennady; Vourganti, Srinivas
Abstract : BACKGROUND: Patients with germline BRCA2 gene mutations (BRCA2 mut ) have more aggressive prostate cancer. Analysis of all reported germline BRCA2 mut prostate cancer cases allows better understanding of the clinicopathologic features and survival outcomes of these men. METHODS: A systematic review was performed with the MEDLINE database to capture articles evaluating clinicopathologic characteristics of men with BRCA2 mut associated prostate cancer. Inclusion criteria were at least five subjects, confirmation of BRCA2 mut status, and data for at least 2 clinical parameters of disease. Meta‐analysis was performed on outcomes data. Chi‐squared tests were used to compare disease features among men undergoing formal versus ad hoc screening, as well as an age of diagnosis less than versus greater than 65 years. Rates of metastatic disease among BRCA2 mut cases were compared to rates among non‐carrier control subjects and the general population using the SEER database. RESULTS: Twelve out of 289 studies met our inclusion criteria, representing 261 BRCA2 mut men. Among carriers, the median age at diagnosis was 62 years and median PSA was 15 ng/dl with 95% of men having a PSA>3. Over 40% of BRCA2 mut patients had T3/T4 disease and over 25% were metastatic at presentation. Survival was worse in BRCA2 mut men with prostate cancer when compared to non‐BRCA2 mut subjects. BRCA2 mut carriers had significantly higher rates of metastatic disease (18%) versus non‐carrier controls (8%) and the SEER population (4%). CONCLUSIONS: BRCA2 mut carriers are more likely to have poor risk of prostate cancer at presentation and exhibit worse oncologic outcomes relative to non‐carriers, including a fourfold increase in metastatic disease. Younger men and those undergoing formal screening present with less advanced disease which supports a need for earlier identification and screening protocols. Additionally, this population may benefit from alternative therapeutic paradigms. Prostate 76:1135–1145, 2016 . © 2016 Wiley Periodicals, Inc.